Site-1 protease regulates skeletal stem cell population and osteogenic differentiation in mice - Patra, Debabrata (Biol Open, 2018)
Site-1 protease (S1P) is a proprotein convertase with essential functions in the conversion of precursor proteins to their active form. In earlier studies, we demonstrated that S1P ablation in the chondrocyte lineage results in a drastic reduction in endochondral bone formation. To investigate the mechanistic contribution of S1P to bone development we ablated S1P in the osterix lineage in mice. S1P ablation in this lineage results in osteochondrodysplasia and variable degrees of early postnatal scoliosis. Embryonically, even though Runx2 and osterix expression are normal, S1P ablation results in a delay in vascular invasion and endochondral bone development. Mice appear normal when born, but by day 7 display pronounced dwarfism with fragile bones that exhibit significantly reduced mineral density, mineral apposition rate, bone formation rate and reduced osteoblasts indicating severe osteopenia. Mice suffer from a drastic reduction in bone marrow mesenchymal progenitors as analyzed by colony-forming unit-fibroblast assay. Fluorescence-activated cell sorting analysis of the skeletal mesenchyme harvested from bone marrow and collagenase-digested bone show a drastic reduction in hematopoietic lineage-negative, endothelial-negative, CD105(+) skeletal stem cells. Bone marrow mesenchymal progenitors are unable to differentiate into osteoblasts in vitro, with no effect on adipogenic differentiation. Postnatal mice have smaller growth plates with reduced hypertrophic zone. Thus, S1P controls bone development directly by regulating the skeletal progenitor population and their differentiation into osteoblasts. This article has an associated First Person interview with the first author of the paper.